Paulo Francis, do teatro à politica: "perdoa-me por me traíres" - Alexandre Torres Fonseca (2001)
This work analyzes, with a political focus, the role of the Brazilian intellectual Paulo Francis in the period between the end of the 1950s and the beginning of the 1960s, until the military coup of 1964. Paulo Francis had a daily column in a major Brazilian newspaper, the Última Hora. First the concept of what it means to be an intellectual is discussed. Then Paulo Francis is shown as an intellectual during three different historical periods. First, at the beginning of his career as a journalist while working as a theater critic he built a cultural model to be followed and also influenced a change in the Brazilian theater scene. During the second period, after his success as a play reviewer, Francis tries to apply the same model to politics with poor results both for himself and for Brazil. We then consider how Francis showed disdain for democratic values, and we examine the pernicious influence of capital on the editorial line of Última Hora, and apparently, also on Francis as a columnist. Finally, we endeavor to show that while writing his memoirs from the 1950s and 1960s Francis twisted some historical facts. The objective of the distortion of reality was to paint with lighter colors his own actions and the action of his leftist-leaning friends' past behavior, thus manufacturing a small part of history in his own image. KEYWORDS: Intellectuals, Paulo Francis, Última Hora, press, 1964 coup d'etat.